2017
DOI: 10.1507/endocrj.ej16-0512
|View full text |Cite
|
Sign up to set email alerts
|

Neutral ceramidase activity inhibition is involved in palmitate-induced apoptosis in INS-1 cells

Abstract: Abstract. Neutral ceramidase (NCDase) is a class of ceramidases, a key enzyme in ceramide degradation. Recently, it was observed that NCDase activity was suppressed by saturated fatty acids to increase ceramide content in rat muscle. However, little is known about its changes in activity and roles in palmitate (Palm)-induced lipotoxicity in pancreatic β cells. Here, we demonstrated that Palm treatment significantly down-regulated NCDase activity, mRNA and protein levels in rat INS-1 cells. In addition, Palm ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…In addition, lipotoxicity induced by prolonged elevated FFAs, particularly saturated FFAs such as palmitate, leads to β -cell apoptosis and dysfunction [ 39 , 40 ]. In agreement with previous studies [ 41 , 42 ], our results showed that exposure to palmitate-induced significant cell death of Ins-1 cells. In addition, palmitate treatment reduced insulin secretion in Ins-1 cells, zebrafish β -cells, and isolated mouse islets.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, lipotoxicity induced by prolonged elevated FFAs, particularly saturated FFAs such as palmitate, leads to β -cell apoptosis and dysfunction [ 39 , 40 ]. In agreement with previous studies [ 41 , 42 ], our results showed that exposure to palmitate-induced significant cell death of Ins-1 cells. In addition, palmitate treatment reduced insulin secretion in Ins-1 cells, zebrafish β -cells, and isolated mouse islets.…”
Section: Discussionsupporting
confidence: 93%
“…Exposure to elevated levels of the saturated FA palmitate induces apoptosis in a range of cells including 3T3 fibroblasts (Kamili et al ., 2015), peripheral blood mononuclear cells (RostamiRad et al ., 2018), human cardiac progenitor cells (Leonardini et al ., 2017), pancreatic β cells (Boslem et al ., 2011; Luo et al ., 2017), macrophages (Kim et al ., 2017), and hepatocytes (Penke et al ., 2017). Palmitate also impairs MDA‐MB‐231 cell proliferation and activates apoptosis (Baumann et al ., 2016; Hardy et al ., 2000, 2003; Kourtidis et al ., 2009; Wu et al ., 2017) via a number of mechanisms, including ER stress (Baumann et al ., 2016; Boslem et al ., 2011), impaired autophagy (RostamiRad et al ., 2018; Wu et al ., 2017), altered NAD metabolism (Penke et al ., 2017), and ceramide synthesis (Luo et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Palmitate also impairs MDA‐MB‐231 cell proliferation and activates apoptosis (Baumann et al ., 2016; Hardy et al ., 2000, 2003; Kourtidis et al ., 2009; Wu et al ., 2017) via a number of mechanisms, including ER stress (Baumann et al ., 2016; Boslem et al ., 2011), impaired autophagy (RostamiRad et al ., 2018; Wu et al ., 2017), altered NAD metabolism (Penke et al ., 2017), and ceramide synthesis (Luo et al ., 2017). Importantly, many of the deleterious effects of palmitate on cellular function are mitigated by cotreatment with other FAs, in particular the monounsaturated FA oleate (Colvin et al ., 2017; Kim et al ., 2017; Penke et al ., 2017; Sargsyan et al ., 2016), which itself is pro‐proliferative and activates phosphoinositide 3‐kinase signaling (Hardy et al ., 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutral ceramidase-degradating ceramides are suppressed by saturated FAs; thus, when there is an excess of saturated FAs, ceramides are accumulated in β-cells [ 212 ]. This leads to the facilitation of apoptosis that is promoted by saturated FAs.…”
Section: Pathology Related To Lcfasmentioning
confidence: 99%